2020
DOI: 10.1371/journal.pone.0241506
|View full text |Cite
|
Sign up to set email alerts
|

Use of long-acting reversible contraception among adolescents and young women in Kenya

Abstract: The Kenya Demographic and Health Survey (KDHS 2014) revealed changing patterns in the contraceptive use of young women aged 15–24, shifting from injectable methods to implants. Long-acting reversible contraception (LARC) is user friendly, long-term, and more effective than other modern methods. It could be a game-changer in dealing with unintended pregnancies and herald a new chapter in the reproductive health and rights of young women. This study determined the factors associated with LARC use among adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
7
20
2
1
Order By: Relevance
“…Previous studies conducted in Arsi Negel 33.5% 16 , 14 Wolaita Zone 38%, 17 Hossana 36.5%, 18 Gondar City 33.7%, 16 Harar City 38%, 19 and Afar Region 33.4% 20 reported the similar finding. The finding was higher than the study done in different parts of Ethiopia, 21 - 25 Kenya, 26 , 27 Uganda 28 and Nepal. 29 Increased utilization of LARCs in this might be due to improved awareness of women on LARCs and differences in study time, setting, and socio-demographic backgrounds.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies conducted in Arsi Negel 33.5% 16 , 14 Wolaita Zone 38%, 17 Hossana 36.5%, 18 Gondar City 33.7%, 16 Harar City 38%, 19 and Afar Region 33.4% 20 reported the similar finding. The finding was higher than the study done in different parts of Ethiopia, 21 - 25 Kenya, 26 , 27 Uganda 28 and Nepal. 29 Increased utilization of LARCs in this might be due to improved awareness of women on LARCs and differences in study time, setting, and socio-demographic backgrounds.…”
Section: Discussioncontrasting
confidence: 70%
“…This is contrary to a study conducted in Kenya that showed more LARC usage among those ages 20–24 y. 46 Increasing LARC usage in SSA countries will require continuous community awareness campaigns to counteract negative perceptions and misinformation. 47 …”
Section: Discussioncontrasting
confidence: 57%
“…Age is a very strong determinant of contraceptive method choice in both short-term and long-term methods because contraceptive intentions of spacing or limiting, which influence the choice of the method, vary significantly with age, hence its influence on continuation and discontinuation. 42 …”
Section: Discussionmentioning
confidence: 99%